El nuevo reporte de sostenibilidad corporativa en el mercado de valores: Apuntes en torno a la cadena de producción y el consumo responsable - Arce Rodríguez, Mario Marcelo (2022)
In this article, the author questions the new corporate sustainability report, issued by Superintendent Resolution 018-2020-SMV/02. In this line, it deals with the meaning of corporate sustainability, or how it should be understood, in the current market. It also highlights the importance of the principle of market transparency with respect to corporate sustainability in the face of the necessary information that investors must have.Focusing on the production chain and responsible consumption, the author evaluates the questions of the form on corporate sustainability issued by the Superintendence of the Stock Market through the standards set by the Ethos-IARSE indicators, as well as by the Global Reporting Initiative. All this to conclude that, although a great step has been taken regarding the information provided, there are still many aspects to specify to reach the current standards on corporate sustainability.